2010
DOI: 10.3171/2010.4.spine09764
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of pullout strength and failure mechanism of posterior instrumentation in normal and osteopenic thoracic vertebrae

Abstract: Bone quality is an important factor that influences stability of posterior thoracic implants. Fixation strength in the osteopenic group was one-fourth of the value measured in vertebrae with good bone quality, irrespective of the instrumentation used. However, in normal bone quality vertebrae, the lamina hook claw system dislocated with significantly less force when compared with other spinal implants. Further studies are needed to investigate the impact of different transpedicular screw designs on the pullout… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
45
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(52 citation statements)
references
References 42 publications
(62 reference statements)
5
45
0
2
Order By: Relevance
“…In vitro average axial pullout forces of non-augmented pedicle screws range from 159 to 663 N [2][3][4]15,16,20,21]. Although the rupture mechanism was different in our experimental setup, including a bending moment, the pullout forces were comparable to the findings of studies performing axial pullout.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…In vitro average axial pullout forces of non-augmented pedicle screws range from 159 to 663 N [2][3][4]15,16,20,21]. Although the rupture mechanism was different in our experimental setup, including a bending moment, the pullout forces were comparable to the findings of studies performing axial pullout.…”
Section: Discussionsupporting
confidence: 65%
“…Reference values for conventional screws without augmentation in normal bone range from 812 to 1546 N [2,[13][14][15]. The results of our preliminary test on the younger specimen fit within this range.…”
Section: Discussionsupporting
confidence: 56%
“…Relationships of various parameters such as the magnitude of corrective forces, number of implants used, degree of correction and implant placement configuration are not yet well understood. Furthermore, it has already been shown by previous studies that too high corrective forces can cause implant breakage or bone fracture which may lead to pullout of screws from the vertebra (Patwardhan et al, 2010;Paxinos et al, 2012). Thus, analysis of corrective forces acting on deformed rod is important to understand the biomechanics of scoliosis correction.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, Paxinos et al [20] demonstrated that pedicle screws and sublaminar wires offer equally strong fixation in normal bone. In contrast, hooks tend to fail with significantly less force.…”
Section: Discussionmentioning
confidence: 99%